REVIEW OF SHARIA ECONOMIC LAW ON THE SALE AND PURCHASE OF PROPERTY AT PT INTAN NIRWANA NUSANTARA HOUSING GOLDEN VIEW IN MAKASSAR CITY - Muhammad Ma'ruf Syafruddin; M. Thahir Maloko; Suriyadi (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2025)
Abstract The labeling of Sharia in a business today is due to the popularity of the term sharia which is free from usury. However, from this, there are still many problems, especially for businesses that only label their business as sharia but in reality do not implement it in accordance with Islamic law. This research is field research which is very close to qualitative research which uses Sharia Economic Law and empirical approaches. The data sources used are primary data sources sourced from the Al-Qur'an, Hadith, Sharia Economic Law Compilation and interviews from PT Intan Nirwana Nusantara Golden View Inn Housing, and secondary data obtained from archive books of property purchases at Golden View Inn Housing. . The research results show that the form of contract implemented by Golden View Inn is the Ishtishna' contract or order which in its implementation is in accordance with the provisions of Sharia Economic Law. Then, regarding the settlement of stalled installments, it is also in accordance with Islamic principles because a deliberation was held to discuss it in good faith first. The implications of this research relate to improving the SPPJB regarding disputes to include the court to be addressed if the good faith process does not run properly. Keywords: Bad Installments, Sharia Economic Law, Istishna.